Peningkatan Kreativitas dan Hasil Belajar Siswa Pada Materi Gereja Menguduskan Dengan Metode PBL Fase F SMAN 1 Siluq Ngurai - Lusia Hari Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research aims to investigate the improvement of students' creativity and learning outcomes on the topic of Sanctifying the Church through the implementation of the Problem-Based Learning (PBL) method in Phase F at SMAN 1 Siluq Ngurai. The study adopts a reflective classroom action research design. The subjects of the research are students of class XI in Phase F at SMAN 1 Siluq Ngurai. Data collection involves observation and tests, and the obtained data are analyzed descriptively. The research findings reveal that the application of the Problem-Based Learning (PBL) model enhances both creativity and learning outcomes of students on the topic of Sanctifying the Church in Phase F at SMAN 1 Siluq Ngurai. This is evidenced by the test results at the end of each cycle, where the score increased from 84% in cycle 1 to 87% in cycle 2. Similar improvements are observed in other indicators. Overall, there is an increase in the average indicator from 77% in cycle 1 to 81% in cycle 2. The students' learning achievements also improved, with the number of students classified as proficient increasing from 83 (25%) in cycle 1 to 5 (42%) in cycle 2. The number of students classified as achieving a satisfactory level decreased from 4 (33%) to 2 (17%). This indicates an improvement of 3 students becoming proficient.